Some up-to-date aspects on the diabetic polyneuropathy - Arnoldo Pérez Rodríguez; Aylin de la Caridad Feria Pérez; Alina Inclán Acosta; Jacqueline Delgado Echezarreta (Centro Provincial de Información de Ciencias Médicas, 2022)
The diabetes mellitus is a chronic disease that can cause multiorganic complications as the diabetic polyneuropathy, with the consequent invalidant disorder to whom suffer from it. For such a reason, an exhaustive literature review was carried out with the objective of upgrading some important aspects on this affection, such as concept, risk factors, pathogenic mechanisms, classification, diagnosis and treatment, among others. It was concluded that this disease is associated with several risk factors, its diagnosis is fundamentally clinical and the glycemic control, the care of feet and the use of medicines are considered as treatment.